The Legal Status of Collective Agreements in England, the United States and Canada - Verge, Pierre (Relations industrielles / Industrial Relations, 1971)
This article reviews "The Legal Status of Collective Agreements in England, the United States and Canada" by B.L. Adell.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z